PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA MATARAM HOTEL) - I MADE MURJANA; NENDY PRATAMA AGUSFIANTO; YUSI FAIZATHUL OCTAVIA (GANEC SWARA, 2021)
Specifically, the purpose of this study was to determine the effect of compensation and motivation on employee performance at the Mataram Lombok hotel. The research is associative, where the respondents are hotel employees, with a multiple linear analysis approach through the SPSS application. The results of the analysis show: (1). the two variables have a partial effect on employee performance, with t-count values of 3.056 (X1) and 2.676 (X2) greater than the t-table value of 2.037. (2). Compensation and motivation variables have a simultaneous effect, this is indicated by the calculated f value of 21.098, which is greater than the value of f table 3.29. based on testing the beta value of the Compensation variable of 0.448, and the value of the motivation variable of 0.392. Based on the value of Tb. it can be said that the compensation variable is more dominant than the motivation variable.